2009
DOI: 10.1021/es9002668
|View full text |Cite
|
Sign up to set email alerts
|

Degradability of an Acrylate-Linked, Fluorotelomer Polymer in Soil

Abstract: Fluorotelomer polymers are used in a broad array of products in modern societies worldwide and, if they degrade at significant rates, potentially are a significant source of perfluorooctanoic acid (PFOA) and related compounds to the environment To evaluate this possibility, we incubated an acrylate-linked fluorotelomer polymer in soil microcosms and monitored the microcosms for possible fluorotelomer (FT) and perfluorinated-compound (PFC) degradation products using GC/MS and LC/MS/MS. This polymer scavenged FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
143
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 28 publications
5
143
1
Order By: Relevance
“…These ''new'' compounds are presented as environmentally friendly alternatives, but they are difficult to remove from drinking water by common treatment techniques and are thought to become the main emerging contributors to total PFC levels in drinking water in the future (Wilhelm et al 2010). Due to their estimated half-life (Washington et al 2009), PFC precursors may constitute an important source of shorter-chained PFCs in the environment for the coming decades.…”
Section: Implications For Human Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…These ''new'' compounds are presented as environmentally friendly alternatives, but they are difficult to remove from drinking water by common treatment techniques and are thought to become the main emerging contributors to total PFC levels in drinking water in the future (Wilhelm et al 2010). Due to their estimated half-life (Washington et al 2009), PFC precursors may constitute an important source of shorter-chained PFCs in the environment for the coming decades.…”
Section: Implications For Human Exposurementioning
confidence: 99%
“…In the environment, some PFCs can degrade through biological or nonbiological processes into perfluoroalkyl carboxylates (PFCAs) and perfluoroalkyl sulfonates (PFASs), which are the two most widely known groups of PFCs, and final degradation products of a variety of PFC precursors, including fluorotelomer alcohols (FTOHs), fluorotelomer sulfonates, perfluorooctane sulfonamidoethanols, and perfluorooctane sulfonamide (Lee et al 2010;Rhoads et al 2008;Washington et al 2009). PFCAs and PFASs do not break down in the environment and thus persist indefinitely.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were collected at a depth of 23 m below the ground surface as described by Washington et al (2009). See the Supporting Information for further details of the analysis.…”
Section: Sample Collection and Microcosm Preparationmentioning
confidence: 99%
“…In a study of the degradation of an acrylate-linked fluorotelomer polymer in soil, Washington et al (2009) observed a loss of recoverable PFOA over time and tentatively identified 2-HPFOA; CF 3 (CF 2 ) 5 CFHCOOH as a possible degradation product of PFOA. The possibility that 2-HPFOA formed in the microcosms in this study was evaluated by extracting microcosms after 740 d of incubation and analyzing these extracts for 2-HPFOA.…”
Section: Confirmation Of Stability In Microcosmsmentioning
confidence: 99%